Winter discharge fluctuations due to ice formation in a Swiss alpine catchment - Nina C. Nagel; Michael Margreth; Florian Lustenberger; David F. Vetsch (Journal of Hydrology: Regional Studies)
Study region: Alpine catchment of the Dischmà stream in canton of Graubünden, Switzerland Study focus: The formation, presence, and melting of ice in alpine streams during winter significantly impacts the dynamics of discharge and ecosystems. This study observed the discharges using wildlife cameras and employed temperature measurements at potential sites in the Dischmà stream to better understand the controls of ice formation and its impact on winter discharge fluctuations. A new algorithm was developed for detection of icing events in the stream and quantification of water retention volumes based on discharge and temperature data whereas the observations were used as ground truth for verification and calibration of the algorithm. New hydrological insights for the region: The discharge data show distinct daily fluctuations ascribed to formation of nocturnal ice, which temporarily impedes or reduces water flow. The specific morphology at the pools with moderate water depth, and step-pool formation facilitated the formation of anchor ice, especially during freezing nights. The proposed event analysis contributes to bridging a gap in hydrological literature for alpine studies, by identifying previously neglected winter stream dynamics, including temporary ice formations. The suggested algorithm can serve as basis for the analysis of such phenomena in alpine streams, offering insights that support data cleaning efforts and further investigations into winter discharge fluctuations, discharge recession, and their ecological impacts.